MORTALITAS DAN PENYUSUTAN BOBOT HIDUP AYAM BROILER DENGAN MANAJEMEN WAKTU PENGANGKUTAN YANG BERBEDA - Zebua, Cipta Kasih Novilita (Program Studi Peternakan Universitas Muhammadiyah Sidenreng Rappang, 2025)
Transportation of broiler livestock is crucial because it determines the welfare of the livestock, especially economic losses due to reduced performance. Transportation of broiler livestock is very influential on mortality and body weight loss as a result of stress during the journey. One thing that can be done to minimize mortality and weight loss is the management of livestock transportation time. The purpose of this study was to determine the effect of transportation time on broiler mortality and body weight loss. Data were analyzed by descriptive analysis to determine the effect of different transportation times on mortality and body weight shrinkage of broiler chickens. The results showed that the transportation of broilers carried out in the morning experienced a shrinkage of 1,43 g while the transportation of broilers carried out in the afternoon experienced a weight loss of 11,71 g. In addition, transportation in the morning had no mortality at all, while transportation in the afternoon had a mortality of 0,29%.